The Impact of Investment Assets, Liquidity, and Firm Size on the Financial Health of General Insurance Companies in Indonesia - Bayu Rafisukmawan (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
This study aims to analyze the influence of Investment Assets, Liquidity, and Firm Size on the health level of general insurance companies in Indonesia, proxied by Risk-Based Capital (RBC). The research employs a quantitative approach using secondary data in the form of financial statements of general insurance companies for the 2020–2024 period. The research sample was obtained using the purposive sampling method, consisting of 20 general insurance companies in Indonesia. The data analysis method used was panel data regression with the assistance of the EViews 13 application. Based on the results of the panel data regression model selection, the best model identified was the Random Effect Model (REM). The results of the study indicate that, partially, Investment Assets and Firm Size do not have a significant effect on the health level of general insurance companies in Indonesia. Meanwhile, Liquidity has a positive and significant effect on the health level of insurance companies proxied by Risk-Based Capital (RBC). Simultaneously, Investment Assets, Liquidity, and Firm Size have a significant effect on the health level of general insurance companies in Indonesia. The findings of this study indicate that liquidity management is an important factor in maintaining the financial stability and solvency of insurance companies. Therefore, insurance companies need to maintain adequate asset liquidity and improve the effectiveness of investment management and risk control in order to sustain the company’s financial health.